1998
DOI: 10.1590/s0074-02761998000300016
|View full text |Cite
|
Sign up to set email alerts
|

Giardia agilis: Ultrastructure of the Trophozoites in the Frog Intestine

Abstract: Intestine samples of Bufo sp. tadpoles with parasitism confirmed for Giardia agilis were studied by transmission electron microscopy. The G. agilis trophozoites were long and thin. The plasma membrane was sometimes undulated and the cytoplasm, adjacent to the dorsal and ventral regions, showed numerous vacuoles. The two nuclei presented prominent nucleoli. The cytoplasm was electron-dense with free ribosomes, glycogen and rough endoplasmic reticulum-like structures. Polyhedral inclusions were observed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…New giant viruses will also likely be isolated from other ecological niches, since VLPs have been reported in a variety of hosts including dinoflagellates (Tarutani et al ., 2001), Giardia muris from hamsters, Giardia duodenalis from domestic rats and Blastocystis sp. from simian faecal material (Sogayar and Gregorio, 1986; 1998; Stenzel and Boreham, 1997). The description of large viruses in eukaryotic species infecting mammalians could bring additional perspectives in terms of host range and, more importantly, evolution and gene exchange between viruses and perhaps with their eukaryotic hosts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New giant viruses will also likely be isolated from other ecological niches, since VLPs have been reported in a variety of hosts including dinoflagellates (Tarutani et al ., 2001), Giardia muris from hamsters, Giardia duodenalis from domestic rats and Blastocystis sp. from simian faecal material (Sogayar and Gregorio, 1986; 1998; Stenzel and Boreham, 1997). The description of large viruses in eukaryotic species infecting mammalians could bring additional perspectives in terms of host range and, more importantly, evolution and gene exchange between viruses and perhaps with their eukaryotic hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Among these VLPs, large particles up to 200 nm long and 100 nm wide were observed in Acanthamoeba sp. cytoplasm (Vickerman, 1962), in various Giardia species (Sogayar and Gregorio, 1986; 1998) and in Blastocystis species (Stenzel and Boreham, 1997). Since these descriptions were based on electron microscopy, the exact nature of these particles remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently eight Giardia species considered to be valid [2]. G. agilis, as one of them, was first reported by Künstler in 1882, and was later detected in the intestines of tadpoles and adults of several anuran amphibian species by other researchers [1,3]. The morphology of G. agilis have been studied based on interference reflexion microscopy and scanning electron microscopy (SEM), and it was shown that the trophozoites of G. agilis have a narrow and elongated body, and the length of their adhesive discs is about one fifth of their body [4].…”
mentioning
confidence: 99%